Early versus Late Admission to Labor Affects Labor Progression and Risk of Cesarean Section in Nulliparous Women - Mikolajczyk, Rafael T.; Zhang, Jun; Grewal, Jagteshwar; Chan, Linda C.; Petersen, Antje; Gross, Mechthild M. (Frontiers in Medicine, 2016)
Background Rates of caesarean section increase worldwide and the components of this increase are partially unknown. A strong role is prescribed to dystocia, at the same time the diagnosis of dystocia is highly subjective. Previous studies indicated that risk of caesarean is higher when women are admitted to the hospital early in the labor. Methods We examined data on 1,202 nulliparous women with singleton, vertex pregnancies and spontaneous labor onset. We selected three groups based on cervical dilatation at admission: early (0.5-1.5 cm, N=178), intermediate (2.5-3.5 cm, N=320) and late (4.5-5.5 cm, N=175). The Kaplan-Meier estimator was used to analyze the risk of delivery by caesarean section at a given dilatation, and thin-plate spline regression with a binary outcome (R library gam) to assess the form of the associations between the caesarean section in either the first or second stage versus vaginal delivery and dilatation at admission. Results Women who were admitted to labor early had a higher risk of delivery by caesarean section (18% versus 4% in the late admission group), while the risk of instrumental delivery did not differ (24% versus 24%). Before 4 cm dilatation, the earlier a woman was admitted to labor, the higher was her risk of delivery by caesarean section. After 4 cm, however, the relationship disappeared. These patterns were true for both first and second stage caesarean deliveries. Conclusion Early admission to labor was associated with a significantly higher risk of delivery by caesarean section during first and second stage. Differential effects of oxytocin augmentation depending on dilation at admission may indicate that admission at the early stage of labor is an indicator rather than a risk factor itself, but admission at the intermediate stage (2.5-3.5 cm) becomes a risk factor itself. Further research is needed to study this hypothesis.